Efficacy of Simulation Using NLN/Jeffries Nursing Education Simulation Framework on Satisfaction and Self-Confidence of Undergraduate Nursing Students in a Middle-Eastern Country - Esra Al Khasawneh RN, MSN, DNSc, FAAN; Judie Arulappan RN, RM, BSN, MSN, PhD, DNSc; Jansi Rani Natarajan RN, BSN, MSN; Savithri Raman RN, BSN, MSN; Chandrani Isac RN, BSN, MSN (SAGE Publishing, 2021)
Introduction Utilizing simulation in nursing education is increasingly becoming a popular teaching pedagogy. Simulation provides opportunity to the nursing students to practice the clinical skills through various real life like situational experiences. Simulation improves the clinical decision making skills of the nursing students. Objective A descriptive, cross sectional, correlational study was conducted to evaluate the efficacy of simulation using NLN/Jeffries Nursing Education Simulation Framework on satisfaction and self-confidence of Undergraduate nursing students. Methods 370 undergraduate nursing students participated in the study. Educational practices, Simulation design, Student satisfaction and Self-confidence questionnaires were used. Results Majority of the nursing students perceived agreement on various domains of student satisfaction, self-confidence, educational practices and simulation design used in the curriculum. The students were self-confident to care for similar patients in the clinical area and satisfied with this instructional method. Satisfaction and self-confidence were correlated with educational practices and simulation design. Conclusion Developing simulations using NLN/Jeffries Nursing Education Simulation framework will provide meaningful, engaging, and pedagogically sound experiences for the students. Pre-briefing and de-briefing are meaningful strategies to enhance the learning of students.